Modeling And Optimization Of Isoamyl Acetate Production In Enzyme Catalyzed Esterification - Hashim, Nur Hamizah Abdul Ghani @ (2011)
Isoamyl acetate is an important substance which is used in various industries including flavour and fragrance industry. The production of this compound using enzymes had attracted many attentions due to its advantages of moderate operating parameters, limited side reactions and easy product recovery. In enzyme catalyzed esterification, acetic acid and isoamyl alcohol are used as substrates to the Candida antarctica immobilized lipase to produce isoamyl acetate. In direct esterification reaction, the ester synthesis is affected by excess water which can change the thermodynamic balance of reaction towards hydrolysis. On the other hand, during the initial stage of the reaction, water activates the enzymes and increases enzyme activity thus increases the reaction rates. Therefore, the amount of water content has been a critical parameter in enzyme catalyzed esterification. Beside this, few parameters considered to affect the process were temperature, enzyme loading, concentration of substrates and reaction time. In order to understand the process and the relationship of these selected parameters, process optimization and model development are essential. The processes optimizations were done via “one-factor-ata- time” and response surface methodology (RSM). The optimum conditions obtained from “one-factor-at-a-time” were compared with RSM and the results were in range. The coefficient of determination, R2 of the RSM model was 0.9448.